2010
DOI: 10.3892/or_00000877
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing peptide promotes the growth of HepG2 cells via EGFR-independent ERK1/2 activation

Abstract: Abstract. Gastrin-releasing peptide (GRP) plays an important role in regulating tumor growth and migration. However, little is known about its role in human hepatocellular carcinoma (HCC) cells. This study explored the effect of GRP on the growth of HCC HepG2 cells and the underlying mechanisms. Expression of GRP and its cognate receptor (GRPR) were detected by immunocytochemisty, reverse transcription-PCR and Western blotting and compared between two human HCC cell lines (HepG2 and MHCC97H) and a normal hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Activation of GRPR has been shown to increase head and neck cancer cell invasion and proliferation by upregulating EGFR transcription and phosphorylating the downstream MAPK pathway [ 350 , 351 ]. Furthermore, autocrine GRP/GRPR activation can directly activate EGFR pre-ligands via Src-dependent cleavage [ 352 ] and then facilitates phosphorylation of EGFR and activation of MAPK pathway [ 353 ]. These findings imply that GRPR cross-talk with EGFR and GRPR inhibition may affect downstream signaling of EGFR by interfering with intracellular EGFR-activated mediators.…”
Section: Key Individual Gpcrs and Their Signaling Pathways Involved In Various Cancermentioning
confidence: 99%
“…Activation of GRPR has been shown to increase head and neck cancer cell invasion and proliferation by upregulating EGFR transcription and phosphorylating the downstream MAPK pathway [ 350 , 351 ]. Furthermore, autocrine GRP/GRPR activation can directly activate EGFR pre-ligands via Src-dependent cleavage [ 352 ] and then facilitates phosphorylation of EGFR and activation of MAPK pathway [ 353 ]. These findings imply that GRPR cross-talk with EGFR and GRPR inhibition may affect downstream signaling of EGFR by interfering with intracellular EGFR-activated mediators.…”
Section: Key Individual Gpcrs and Their Signaling Pathways Involved In Various Cancermentioning
confidence: 99%
“…GRPR overexpression has been evidenced in a wide spectrum of tumors such as 63 to 100% of prostate, 33 to 72% of breast and 76 to 93% of gastric cancers [4][5][6][7]. Many studies have highlighted that the GRPR pathway is a key actor of cancer progression through increasing proliferation, invasion and migration of cancer cells via autocrine and paracrine pathways [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TAPI-1 has been proposed to ameliorate various inflammatory diseases, such as rheumatoid arthritis, kidney injury, and neuroinflammation [ 8 10 ]. Additionally, several studies showed that TAPI-1 might display anti-tumor efficacy in pancreatic cancer, breast cancer, and hepatoma [ 11 15 ]. However, the effect of TAPI-1 on digestive tract tumors remains to be greatly elucidated.…”
Section: Introductionmentioning
confidence: 99%